Dwaj satyrycy o wyrodnych potomkach zacnych przodków: Krzysztof Opaliński i Adam Naruszewicz - Obremski, Krzysztof (Śląskie Studia Polonistyczne, 2015)
Both analysed satires, the one from the mid-17th century and the other written one hundred years later, are connected by a relationship of “incompatible compatibility”; after all, their authors presented as reprehensible what they saw differently: whereas Opaliński criticized lower gentry and upper gentry, Naruszewicz criticised only the latter. The most general meaning of both texts is as follows: the idea of nobility and its social practice are usually divergent, and therefore, opposing. Both satirists can be regarded as republicans, yet, this ideological bond is undermined by the radicalism of the descendant of an aristocratic family and moderate democratism of the Pińsk master of the hunt.